Efeitos do uso da irradiação e de antioxidantes na estabilidade da carne moída refrigerada - Daniel Rezende Xavier (2011)
The main objective of this study is to evaluate the effects of gamma irradiation (4,5 kGy) and sodium eritorbate in conventional-packed ground beef. The samples were stored under refrigeration (2ºC) for 42 days and different physico-chemical, color and lipid oxidation (TBARS) analyses were conducted. There were no significant changes in meat composition during the 42 days of storage. The pH values were maintained in acceptable values for the association of irradiation and antioxidants. This association were also with statistic differences for prevent lipid oxidation in irradiated samples in 16 and 42 days of storage. Lipid oxidation was higher in samples irradiated with 4,5 kGy and antioxidants were efficient to maintain the levels of lipid oxidation in samples irradiated.